The diagnostic performance evaluation of the SD BIOLINE HIV/syphilis Duo rapid test in southern Ethiopia: a cross-sectional study. Issue 4 (23rd April 2015) - Shimelis, Techalew; Tadesse, Endale
Abstract : Objective: To determine the diagnostic performance of the SD BIOLINE HIV/syphilis Duo rapid test. Design: A hospital-based cross-sectional study. Setting: This evaluation was conducted at one of the largest hospitals in southern Ethiopia. Participants: Serum samples obtained from clients attending the antiretroviral therapy and voluntary counselling and testing centres were used. Sera were originally collected for the purpose of investigating syphilis epidemiology. The performance of the test to detect HIV was evaluated using 400 sera (200 HIV positives and 200 HIV negatives). Also, its performance to detect syphilis was evaluated using 85 syphilis positive and 100 syphilis negative serum samples. Individuals <15 years of age or syphilis treated or those with ≤50 cells/µL CD4 cell count were originally excluded. Outcome measures: HIV screening was carried out according to the national rapid diagnostic testing (RDT) algorithm: Shenghai Kehua Bioengineering (KHB) test kit as a screening test, followed by the HIV1/2 STAT-PAK assay if positive. Where the result of the STAT-PAK is discordant with KHB, Unigold HIV is used as a tiebreaker to determine the result. We also used ELISA to resolve discordant HIV results. Syphilis serostatus was determined using the Treponema pallidum haemagglutination assay (TPHA). Results: The respective sensitivity, specificity, positive predictive value and negative predictive value of the SD BIOLINE HIV/syphilis Duo test were 100, 99.5, 99.5 and 100% for HIV and 97.6, 96, 95.4 and 98% for syphilis testing, respectively. In reference to TPHA, the test kit reported 4 false positives and 2 false negative results for syphilis. The κ values were 0.99 for HIV testing and 0.94 for syphilis testing. Conclusions: The excellent performance of the SD BIOLINE HIV/syphilis Duo test to detect HIV as well as syphilis facilitates the integration of syphilis testing and treatment to the already established HIV prevention programme, ultimately contributing to the dual HIV and syphilis elimination goal.